Two Literary Genres, One Work: A Chronogram Poem by Ḥaḳḳī in Rüknī’s Versified Dictionary - Toy, Saliha (Keshif, 2024)
Two Literary Genres, One Work: A Chronogram Poem by Ḥaḳḳī in Rüknī’s Versified Dictionary